Bridging Synaptic and Epigenetic Maintenance Mechanisms of the Engram - Kyrke-Smith, Madeleine; Williams, Joanna M. (Frontiers in Molecular Neuroscience, 2018)
How memories are maintained, and how memories are lost during aging or disease, are intensely investigated issues. Arguably, the reigning theory is that synaptic modifications allow for the formation of engrams during learning, and sustaining engrams sustains memory. Activity-regulated gene expression profiles have been shown to be critical to these processes, and their control by the epigenome has begun to be investigated in earnest. Here, we propose a novel theory as to how engrams are sustained. We propose that many of the genes that are currently believed to underlie long-term memory are actually part of a ‘plasticity transcriptome’ that underpins structural and functional modifications to neuronal connectivity during the hours to days following learning. Further, we hypothesise that a ‘maintenance transcriptome’ is subsequently induced that includes epigenetic negative regulators of gene expression, particularly histone deacetylases. The maintenance transcriptome negatively regulates the plasticity transcriptome, and thus the plastic capability of a neuron, after learning. In this way, the maintenance transcriptome would act as a metaplasticity mechanism that raises the threshold for change in neurons within an engram, helping to ensure the connectivity is stabilized and memory is maintained.